Assessment of Local Cultivars of Nightshade (Solanum macrocarpon L.) in Benin - Ezin, Vincent Awe; Saka, M.; Ahoton, E.L.; Quenum, F.; Ayenan, Matthieu (My University, 2017)
Solanum macrocarpon (L.) commonly known as “Gboma” is a leafy vegetable widely eaten in several countries of West Africa and South America. Despite the importance of gboma in Africa, this plant is still neglected and underutilized. An understanding of the diversity and characteristics of the existing local cultivars would help value this vegetable crop. The present study aims to characterize local cultivars of S. macrocarpon. Therefore, 51 local cultivars of S. macrocarpon collected from 24 communes of Benin were grown in a randomized alpha lattice design with five (5) incomplete blocks and three (3) replications. Data were collected on 23 variables including 14 quantitative and nine (9) qualitative traits. The results of analysis of variance (ANOVA) revealed a very highly significant difference for all quantitative traits (P <0.001) and showed that there was a significant diversity amongst the collected samples. The hierarchical ascending classification generated a dendrogram which grouped the 51 local cultivars into four (4) different classes. The cultivars of class 2 had the highest values for the useful biomass and total biomass. Those in class 4 had the highest values for the leaf length, leaf width, leaf area, fruit length and width. After analysis, it appears that the cultivars of Class 2 and 4 showed the best leaf traits. Thus, local cultivars 13; 42; 19; 47; 39; 4; 12; 1; and 38 may be used as potential parents in future breeding programs and improvement of S. macrocarp
Keywords: S. macrocarpon; local cultivars; genetic variability; characterization; Benin.